Surgery for acute Type I aortic dissection without resection of supra-aortic entry sites leads to unfavourable aortic remodelling. (29th January 2018) - Heo, Woon; Song, Suk-Won; Lee, Kwang-Hun; Lee, Shin-Young; Kim, Tae-Hoon; Baek, Min-Young; Yoo, Kyung-Jong
Abstract: OBJECTIVES: This study aimed to evaluate the impact of remnant re-entries in arch branches on postoperative change in the aortic arch and descending aortic diameters and the rate of major adverse aortic events. METHODS: Between January 2010 and December 2016, 249 patients underwent surgery for acute Type I aortic dissection. Patients who underwent total arch replacement, had Marfan syndrome or had intramural haematoma were excluded. Seventy-two patients with predischarge and follow-up computed tomography scans were enrolled. Patients with and without re-entries in the arch branches after surgery were assigned to the supra-aortic entry (SAE, n = 21) and no supra-aortic entry ( n = 51) groups, respectively. Diameters were measured at 7 levels: the innominate artery, left common carotid artery, left subclavian artery, 20 mm distal to the left subclavian artery, pulmonary artery bifurcation, coeliac axis and maximal diameter of the descending thoracic aorta. RESULTS: Growth rates at the levels of the pulmonary artery bifurcation and 20 mm distal to the left subclavian artery were significantly higher in the SAE group than in the no supra-aortic entry group. The rate of freedom from major adverse aortic events (annual growth >5 mm or maximal diameter of the descending thoracic aorta >50 mm) at 5 years was significantly higher in the no supra-aortic entry group than in the SAE group. CONCLUSIONS: Remnant SAE leads to unfavourable aortic remodelling after acute Type I aortic dissection repair.